2009
DOI: 10.1097/shk.0b013e3181997173
|View full text |Cite
|
Sign up to set email alerts
|

Hmgb1 Is Markedly Elevated Within 6 Hours of Mechanical Trauma in Humans

Abstract: High-mobility group box 1 (HMGB1) is a late mediator of the systemic inflammation associated with sepsis. Recently, HMGB1 has been shown in animals to be a mediator of hemorrhage-induced organ dysfunction. However, the time course of plasma HMGB1 elevations after trauma in humans remains to be elucidated. Consequently, we hypothesized that mechanical trauma in humans would result in early significant elevations of plasma HMGB1. Trauma patients at risk for multiple organ failure (ISS ≥15) were identified for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 28 publications
(45 reference statements)
14
140
4
3
Order By: Relevance
“…Previous studies have reported the release of HMGB1 by ECs following RAGE ligation; however, whether or not HMGB1 is released as a result of cellular activation or necrosis of endothelium has not been described (13,36). Our findings are consistent with previous reports demonstrating elevated HMGB1 levels in patients receiving PRBC transfusions (21). Posttransfusion levels of HMGB1 were higher than what has been reported in transfusates, suggesting that HMGB1 is secreted or released as part of the response to RBC transfusion (21).…”
Section: L259supporting
confidence: 61%
“…Previous studies have reported the release of HMGB1 by ECs following RAGE ligation; however, whether or not HMGB1 is released as a result of cellular activation or necrosis of endothelium has not been described (13,36). Our findings are consistent with previous reports demonstrating elevated HMGB1 levels in patients receiving PRBC transfusions (21). Posttransfusion levels of HMGB1 were higher than what has been reported in transfusates, suggesting that HMGB1 is secreted or released as part of the response to RBC transfusion (21).…”
Section: L259supporting
confidence: 61%
“…HMGB1 has been reported as a major DAMP released during trauma 34 and presents at a high concentration in bone marrow. 35 To address whether HMGB1 mediates tissue damagesuppression of Mϕ necroptosis in response to LPS, we prepared HMGB1-deficient BCM from femurs and tibias harvested from inducible HMGB1-knockout mice 36 ( Figure 3a), and used the HMGB1-deficient BCM to treat BMDM.…”
Section: Resultsmentioning
confidence: 99%
“…Peltz and colleagues in their study observed thirty times elevation of plasma HMGB1 levels after trauma compared to healthy controls during 1 h period of injury, which stabilized at 2 -6 h post-injury [20]. Cohen and colleagues found a compelling distinction in plasma levels of HMGB1 among survivors and nonsurvivors from severe trauma.…”
Section: Hmgb1 As a Biomarkermentioning
confidence: 96%